Chemical warfare agents - K Ganesan; S K Raza; R Vijayaraghavan (Journal of Pharmacy and Bioallied Sciences, 2010)
Among the Weapons of Mass Destruction, chemical warfare (CW) is probably one of the most brutal created by mankind in comparison with biological and nuclear warfare. Chemical weapons are inexpensive and are relatively easy to produce, even by small terrorist groups, to create mass casualties with small quantities. The characteristics of various CW agents, general information relevant to current physical as well as medical protection methods, detection equipment available and decontamination techniques are discussed in this review article. A brief note on Chemical Weapons Convention is also provided.